2018
DOI: 10.1016/j.apcatb.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SO2-poisoning over the lifetime of a Cu-CHA catalyst for NH3-SCR

Abstract: Highlights Deactivation of Cu-CHA catalysts for NH3-SCR by SO2 occurs fast. Deactivation by SO2 can be limited to 20 % by regeneration at 550 °C. Regeneration probably feasible for handling SO2-poisoning of Cu-CHA SCR catalysts. SO2-poisoning appears to depend on the structural properties of Cu-CHA materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 24 publications
(80 reference statements)
4
51
0
Order By: Relevance
“…14 Deactivation by SO2 is almost immediate: at about 1% of the total lifetime exposure to SO2, the activity is reduced to about 30% of the original activity, and it stabilizes at about 10% of the original activity after 5-10% of the lifetime SO2 exposure. 17 The sulfur uptake in the Cu-CHA catalyst follows a similar pattern as the activity and, dependent on the temperature, a maximum S/Cu molar ratio of 0.5-1 is reached. The observation that the S/Cu ratio usually does not exceed 1 points to the formation of Cu,S species.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…14 Deactivation by SO2 is almost immediate: at about 1% of the total lifetime exposure to SO2, the activity is reduced to about 30% of the original activity, and it stabilizes at about 10% of the original activity after 5-10% of the lifetime SO2 exposure. 17 The sulfur uptake in the Cu-CHA catalyst follows a similar pattern as the activity and, dependent on the temperature, a maximum S/Cu molar ratio of 0.5-1 is reached. The observation that the S/Cu ratio usually does not exceed 1 points to the formation of Cu,S species.…”
Section: Introductionmentioning
confidence: 65%
“…Ultra-low sulfur diesel contains less than 10 wt ppm (Europe) or 15 wt ppm (US) sulfur, and the SO2 concentration in the exhaust gas typically reaches a few ppmv, which is nevertheless sufficient to reduce the low-temperature activity of the Cu-CHA catalysts significantly. [13][14][15][16][17][18][19][20][21][22][23][24] To be able to preserve the good lowtemperature activity, it is important to understand the impact of SO2 on the NH3-SCR activity of Cu-CHA based catalysts. We have recently shown that deactivation of Cu-CHA catalysts depends on the total SO2 exposure, which is the product of the SO2 concentration and the exposure time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that transition metal oxides such as FeO X , CuO X , MnO X, and NiO X can be used as active components to catalyze NO X reduction. For example, deNO X performance over Cu‐zeolite catalysts showed high NO X conversion in a temperature range of 180–300 °C and Mn/biomass‐char catalysts could achieve NO conversion as high as 87.6 % at 200 °C . Combining Mn and Fe can create a synergistic effect in which more than 90 % NO X conversion can be maintained while using a temperature range of 200–250 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Removal of NO x by reduction is an extraordinary efficient method for removing NO x . However, SCR is limited by a series of problems, such as high cost, high temperature at 300 • C, NH 3 escaping from secondary pollution environment [213], poor sulfur and water resistance of catalysts and susceptibility to poisoning and inactivation [214,215], which affect the life of the catalysts, makes the treatment and operation cost significantly higher [216,217]. Therefore, how to promote the resource-saving and environmentally friendly denitrification process is a difficult problem to be solved urgently in the world [218].…”
Section: H 2 -Scrmentioning
confidence: 99%